2015
DOI: 10.4172/2165-7890.1000154
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dietary Intake and Nutritional Status in Children with Autism Spectrum Disorder

Abstract: Parents and caregivers of children with Autism Spectrum Disorder (ASD) often report that their children are picky, restricted, and problem eaters. Additionally, it has been reported that children with ASD often experience gastrointestinal problems such as constipation, diarrhea, flatulence, cramping, bloating, and diffuse pain. These factors raise concern for nutritional status of children with ASD, given that the refusal to consume particular foods coupled with the inability to tolerate, digest, and absorb th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…Selective eating and food aversion were also found among children with ASD. Children with ASD tend to prefer the same food repeatedly, which can result in a severely imbalanced diet (Barnhill et al, 2015). Research conducted by Evans et al (2012) has found that children with ASD consume more sweetened beverages and snacks, and fewer fruits and vegetables than typically developing children, which resembled our study outcomes.…”
Section: Discussionsupporting
confidence: 73%
“…Selective eating and food aversion were also found among children with ASD. Children with ASD tend to prefer the same food repeatedly, which can result in a severely imbalanced diet (Barnhill et al, 2015). Research conducted by Evans et al (2012) has found that children with ASD consume more sweetened beverages and snacks, and fewer fruits and vegetables than typically developing children, which resembled our study outcomes.…”
Section: Discussionsupporting
confidence: 73%
“…Of particular interest to the present study is the influence of behavioural ridgity in restricted eating habits, which can be manifested by rituals in preparation and presentation (Jacobi et al, 2008). These factors are also indicative to those on the Autistic spectrum, and research has shown that childhood food neophobia is higher in those populations (Bandini et al, 2010;Barnhill et al, 2015). However, what remains unclear is to what extent these sorts of traits (i.e.…”
Section: Introductionmentioning
confidence: 95%
“…15 In a cross-sectional study of children with autism, dietary intake of vitamins A, B1, B12, D, and folate, calcium, magnesium, potassium, iodine, omega-3, omega-6, linoleic acid, and α-linolenic acid was found insufficient. 16 In a study conducted on children with ASD, it was seen that there was suboptimal nutrient intake. Vitamin D, calcium, and bone health should be taken care of.…”
Section: Medical Treatment Of Asdmentioning
confidence: 99%